A century of decline: Loss of genetic diversity in a southern African lion‐conservation stronghold. Issue 6 (11th March 2019) - Dures, Simon G.; Carbone, Chris; Loveridge, Andrew J.; Maude, Glyn; Midlane, Neil; Aschenborn, Ortwin; Gottelli, Dada
Abstract: Aim: There is a dearth of evidence that determines the genetic diversity of populations contained within present‐day protected areas compared with their historical state prior to large‐scale species declines, making inferences about a species' conservation genetic status difficult to assess. The aim of this paper was to demonstrate the use of historical specimens to assess the change in genetic diversity over a defined spatial area. Location: Like many other species, African lion populations ( Panthera leo ) are undergoing dramatic contractions in range and declines in numbers, motivating the identification of a number of lion‐conservation strongholds across East and southern Africa. We focus on one such stronghold, the Kavango–Zambezi transfrontier conservation area (KAZA) of Botswana, Namibia, Zambia and Zimbabwe. Methods: We compare genetic diversity between historical museum specimens, collected during the late 19th and early 20th century, with samples from the modern extant population. We use 16 microsatellite markers and sequence 337 base pairs of the hypervariable control region (HVR1) of the mitochondrial genome. We use bootstrap resampling to allow for comparisons between the historical and modern data. Results: We show that the genetic diversity of the modern population was reduced by 12%–17%, with a reduction in allelic diversity of approximately 15%, compared to historical populations, in addition to having lost a number of mitochondrial haplotypes. We also identify a number of "ghost alleles" in the historical samples which are no longer present in the extant population. Main Conclusions: We argue a rapid decline in allelic richness after 1895 suggests the erosion of genetic diversity coincides with the rise of a European colonial presence and the outbreak of rinderpest in the region. Our results support the need to improved connectivity between protected areas in order to prevent further loss of genetic diversity in the region.